Tolerance and intolerance in early Judaism and Christianity - Stanton, Graham; Sṭrumzah, Gedalyahu Gʹ. (Cambridge University Press, 1998)
The essays in this book consider issues of tolerance and intolerance faced by Jews and Christians between approximately 200 BCE and 200 CE. Several chapters are concerned with many different aspects of early Jewish-Christian relationships. Five scholars, however, take a difference tack and discuss how Jews and Christians defined themselves against the pagan world. As minority groups, both Jews and Christians had to work out ways of co-existing with their Graeco-Roman neighbours. Relationships with those neighbours were often strained, but even within both Jewish and Christian circles, issues of tolerance and intolerance surfaced regularly. So it is appropriate that some other contributors should consider 'inner-Jewish' relationships, and that some should be concerned with Christian sects.